2010
DOI: 10.1093/humrep/deq003
|View full text |Cite
|
Sign up to set email alerts
|

Trends in delivery and neonatal outcome after in vitro fertilization in Sweden: data for 25 years

Abstract: The decrease in unwanted outcomes can, to a large extent, be explained by the reduced rate of multiple births but was seen also among singletons. Other explanations can be sought in changes in the characteristics of patients undergoing IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 10 publications
1
63
0
5
Order By: Relevance
“…Following ART, multiple birth rates are between 25% and 50% (Martin et al, 2009;Sunderam et al, 2009;de Mouzon et al, 2010). Single embryo transfer (SET) can significantly decrease the multiple birth rates (Gerris, 2009;Källén B. et al, 2010b), particularly because the blastocyst culture can dramatically increase the likelihood of embryo implantation (Papanikolaou et al, 2008). SET is increasing in popularity in resent years.…”
Section: Neonatal Outcomesmentioning
confidence: 99%
“…Following ART, multiple birth rates are between 25% and 50% (Martin et al, 2009;Sunderam et al, 2009;de Mouzon et al, 2010). Single embryo transfer (SET) can significantly decrease the multiple birth rates (Gerris, 2009;Källén B. et al, 2010b), particularly because the blastocyst culture can dramatically increase the likelihood of embryo implantation (Papanikolaou et al, 2008). SET is increasing in popularity in resent years.…”
Section: Neonatal Outcomesmentioning
confidence: 99%
“…this reported increase in mZt does not occur in all blastocyst transfer programmes (moayeri et al, 2007; papanikolaou et al, 2010); however, a notable recent analysis of a large number of cycles on the Society for assisted reproductive technologies (Sart) database confirmed the association between blastocyst transfer and increased incidence of mZt (luke et al, 2014). the causal factors are as of yet unknown and couples should be counselled about the possible increased risk of mZt in each particular clinic of blastocyst, compared (Kallen et al, 2010b). the underlying cause of this phenomenon is unknown, but may include altered allocation of cells to the placenta in blastocysts developing in vitro.…”
Section: Blastocyst Assessment and Transfermentioning
confidence: 99%
“…Sweden continues to report the highest percentage of Set at 69.9 %. In 2010, Kallen et al (2010b) examined trends in delivery and neonatal outcome from the Swedish national heath register dataset spanning over 25 years. the study included in excess of 25,000 women receiving Ivf treatment over the 5-year period following the introduction of eSet and showed that the risk of neonatal death and morbidity was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In older mothers, where the risk is lower, it was recommended that no more than two embryos should be transferred. These recommendations have been shown elsewhere in Europe to maintain the live birth rates following IVF but significantly lower the rate of multiple births, particularly of higher plurality (6). In 2015, the HFEA published a report detailing a significant reduction in the rate of multiple birth pregnancies in the UK since the publication in 2008, reduced from 1 in 4 in 2008 to 1 in 6 in 2013 (7).…”
Section: Introductionmentioning
confidence: 99%